Analysis of the Effectiveness of Solar Panel Systems in Electricity Using the Fmea Method on Smokeless Waste Burning Machines - Afriadi, Reza Tri; Naubnome, Viktor; Kardiman, Kardiman (Journal of Education Technology Information Social Sciences and Health, 2024)
This research has been carried out on the analysis of the effectiveness of solar panel systems in electricity using the FMEA method on smokeless waste burning machines. This research aims to determine the problems and causes that occur in the electrical failure of solar panels in smokeless waste burning machines. This research also aims to implement and find out how effective the Failure Mode And Effect Analysis (FMEA) method is in reducing the risk of electrical power failure in the panel system. solar energy on smokeless waste burning machines. This research also analyzes the effect of damage and data processing using the FMEA method to determine the intensity of solar radiation in measurements using a luxmeter. Temperature measurements were carried out on the solar panels using a thermogun, for voltage and current measurements using a digital multimeter, while for measuring the intensity of sunlight using a luxmeter. The temperature test results in sunny weather were 39.3oC at 9:07, 42.4oC at 12:07, 34.9oC at 15:07 while in cloudy weather it was 38.5oC at 09:07, 40.3oC at 12:07, 36.9oC at 15:07. Electrical power is very different when collecting data in sunny conditions and cloudy conditions, therefore in this study the differences will be tested after and before fanning so that it can be easier to determine the effectiveness of the electrical power produced. The increase in temperature on the surface of the solar panel greatly influences the output voltage and current of the solar panel which has an impact on the output power of the solar panel. Temperatures from 09:07 to 15:07 can result in a decrease in the power produced by the solar panel, but at At the same time, the surface of the solar panel is cooled using a fan for 5 minutes, then the power produced by the solar panel directly experiences the highest increase at 11:00 with an increase in power of 3.53 watts. In accordance with the flow diagram for making FMEA for the system, several types of damage or failure that often occur in solar panel systems are collected based on several studies. Information regarding the severity level, number of occurrences and how a method can detect errors in solar power generation systems was obtained from several previous research literature and discussions with PLTS practitioners. The S, D, O values are then multiplied to get the Risk Priority Number (RPN) results which indicate which failures have a large RPN. From this mapping we can take further action to overcome failures in the solar panel system. From the results of the FMEA test analysis, it is very useful in finding out deficiencies or causes of failure in the electricity produced, in this tool there is damage to use or damage to the tool or room factors which can interfere with the process of ineffectiveness of the solar panels that produce electricity in smokeless waste burners. This.